Changes in the functional diversity of birds due to habitat loss in the Brazil Atlantic Forest - Mariano-Neto, Eduardo; Santos, Rafael A. S. (Frontiers in Forests and Global Change, 2023)
Landscape changes due to habitat loss and fragmentation can result in complex changes in biodiversity and functional diversity. On the other hand, the functional diversity changes also reflect the modifications in the ecosystem functions, patterns of resources use by the species, and species interactions. In the present work, we evaluated how habitat loss at a landscape scale influences the functional diversity of different bird communities (total community, frugivorous, and insectivorous birds) in landscapes of 5–60% of forest cover in the Bahia Atlantic Forest. In a sample design that aimed to minimize the effects of some landscape-scale possible bias, we randomly selected twelve 6 km × 6 km landscapes, and we surveyed eight plots randomly located in forested areas within each landscape. We focused on the species classified as forest-dependent. We calculated the total richness and each species’ relative abundance in each landscape. To evaluate functional diversity, 19 functional traits were chosen for the total community, 11 for the frugivore birds, and 12 for the insectivore birds. The choice of traits represents how species use their resources and the use of these in other studies of functional diversity. As biodiversity changes to habitat loss could be non-linear, we evaluated the response pattern of bird functional diversity to habitat loss using three different metrics (FRic, FEve, and FDiv) for all communities (total community, frugivorous and insectivorous birds). Model selection was used to evaluate the response models (null, linear, and logistical). Our results indicated that as forest amount decreases, we found a sharp decrease in FRic, significantly below 30% forest cover. That suggests a reduction in resource use by species in those landscapes. FEve also showed a sharp decline in landscapes below 15% of habitat, indicating a possible reduction in the structural complexity. Fdiv also decreases dramatically in landscapes below 15% of forest amount, which suggests a decrease in functional dissimilarity between species, probably due to environmental filtration, which can lead to taxonomic homogenization. Therefore, we assessed the importance of forests for providing the resources for the permanence of species and their functions, and as a population source. Our study provides quantitative indicators of the relationship between functional diversity and habitat loss, which can be crucial in implementing more robust conservation actions to preserve the Atlantic Forest and its ecosystem services.